2011
DOI: 10.3109/0886022x.2011.615966
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Dialysis Dependence in Critically Ill Patient Survivors of Acute Kidney Injury

Abstract: Background: Acute kidney injury is a common disorder in critical ill patients and it is associated with high mortality. Few studies focus on long-term perspectives such as health-related quality of life (HRQOL) and dialysis dependence. Methods: Prospective cohort study at the intensive care unit (ICU) of a Brazilian tertiary hospital. All patients requiring dialysis over a 2-year enrollment period were included. The Medical Outcomes Study 36-Item Short Form Health Survey (SF-36) assessed the HRQOL along with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Several previous studies have reported lower HRQoL among RRT patients compared to matched general population [20,21]. Morsch et al [34] found that younger and less severely ill RRT-treated patients had better HRQoL as measured with the SF-36 instrument than older patients with long hospital stay. Johansen et al [35] reported an extremely low HRQoL among 60-day survivors after RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported lower HRQoL among RRT patients compared to matched general population [20,21]. Morsch et al [34] found that younger and less severely ill RRT-treated patients had better HRQoL as measured with the SF-36 instrument than older patients with long hospital stay. Johansen et al [35] reported an extremely low HRQoL among 60-day survivors after RRT.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] A number of studies have indicated that the QOL of dialysis patients is greatly impaired compared to general population. 10,11 However, differences in QOL between PD and HD patients have not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that despite of socioeconomic differences with possible variations in health status and outcomes across the world21, 22 ) , physical component is more compromised than mental component as also reported by Hofhuis et al9 ) . Moreover, the influence of age has been encountered in other studies, including those from developing countries13, 14 ) .…”
Section: Discussionmentioning
confidence: 97%
“…A Brazilian study13 ) assessed QoL of critically ill survivors who presented acute kidney injury. It was a large cohort study, which found that chronic kidney injury, septic shock, older age and longer ICU stay were related to worse QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation